BLUE OCEAN STRATEGY : SEBUAH UPAYA KELUAR DARI PERSAINGAN - Nina Septina (Bina Ekonomi, 2007)
A competition in business  is like a never ending war. Market competitions arc getting  tighter  in every single aspect. Many efforts had been done to win  the battle. This one called Red Ocean  Strategy, where every player tries hard  to compete and beat the competition.  The winner still has  to survive  their position in the existing market,  to keep away from being shadowed  by the competitor.  The term Blue Ocean  sounds new, but its existence is not.  lt is a feature of business  life, past and present. value  innovation is the cornerstone of blue ocean strategy.  The core of this paper  is about  the analytical  tools and frameworks  of blue ocean strategy which are The Strategy Canvas, The Four Actions Framework and The Eliminate-Reduce-Rai*-Create Grid.